Effect of dapagliflozin on ferroptosis through the gut microbiota metabolite TMAO during myocardial ischemia–reperfusion injury in diabetes mellitus rats - Lian Wang; Yao Wang; Heng Xu; Wenyuan Li (Scientific Reports, 2024)
Abstract Dapagliflozin (DAPA) demonstrates promise in the management of diabetic mellitus (DM) and cardiomyopathy. Trimethylamine N-oxide (TMAO) is synthesized by the gut microbiota through the metabolic conversion of choline and phosphatidylcholine. Ferroptosis may offer novel therapeutic avenues for the management of diabetes and myocardial ischemia–reperfusion injury (IRI). However, the precise mechanism underlying ferroptosis in cardiomyocytes and the specific role of TMAO generated by gut microbiota in the therapeutic approach for DM and myocardial IRI utilizing DAPA need to be further explored. Nine male SD rats with specific pathogen-free (SPF) status were randomly divided equally into the normal group, the DM + IRI (DIR) group, and the DAPA group. The diversity of the gut microbiota was analyzed using 16S rRNA gene sequencing. Additionally, the Wekell technique was employed to measure the levels of TMAO in the three groups. Application of network pharmacology to search for intersection targets of DAPA, DIR, and ferroptosis, and RT-PCR experimental verification. Ultimately, the overlapping targets that were acquired were subjected to molecular docking analysis with TMAO. The changes of Bacteroidetes and Firmicutes in the gut microbiota of DIR rats were most significantly affected by DAPA. Escherichia-Shigella and Prevotella_9 within the phylum Bacteroidetes could be identified as the primary effects of DAPA on DIR. Compared with the normal group, the TMAO content in the DIR group was significantly increased, while the TMAO content in the DAPA group was decreased compared to the DIR group. For the network pharmacology analysis, DAPA and DIR generated 43 intersecting target genes, and then further intersected with ferroptosis-related genes, resulting in 11 overlapping target genes. The mRNA expression of ALB, HMOX1, PPARG, CBS, LCN2, and PPARA decreased in the DIR group through reverse transcription polymerase chain reaction (RT-PCR) validation, while the opposite trend was observed in the DAPA group. The docking score between TMAO and DPP4 was − 5.44, and the MM-GBSA result of − 22.02 kcal/mol. It epitomizes the finest docking performance among all the target genes with the lowest score. DAPA could reduce the levels of metabolite TMAO produced by gut microbiota, thereby regulating related target genes to decrease ferroptosis in DIR cardiomyocytes.